SACCHARIFICATION OF NATIVE CASSAVA STARCH AT HIGH DRY SOLIDS IN AN ENZYMATIC MEMBRANE REACTOR - I Nyoman Widiasa; I Gede Wenten (Reaktor, 2009)
This study is aimed to develop a novel process scheme for hydrolysis of native cassava starch at high dry solids using an enzymatic membrane reactor (EMR). Firstly, liquefied cassava starch having solids content up to 50% by weight was prepared by three stage liquefactions in a conventional equipment using a commercially available heat stable a-amylase (Termamyl 120L). The liquefied cassava starch was further saccharified in an EMR using glucoamylase (AMG E). By using the developed process scheme, a highly clear hydrolysate with dextrose equivalent (DE) approximately 97 could be produced, provided the increase of solution viscosity during the liquefaction was precisely controlled. The excessive space time could result in reduction in conversion degree of starch. Moreover, a residence time distribution study confirmed that the EMR could be modelled as a simple continuous stirred tank reactor (CSTR). Using Lineweaver-Burk analysis, the apparent Michaelis-Menten constant (Km) and glucose production rate constant (k2) were 552 (g/l) and 4.04 (min-1), respectively. Application of simple CSTR model with those kinetic parameters was quietly appropriate to predict the reactor’s performance at low space time.